PENYULUHAN TENTANG ALUR PELAYANAN DI RUMAH SAKIT SERTA PROTOKOL KESEHATAN BAGI PASIEN YANG DITERAPKAN DI RUMAH SAKIT TAHUN 2021 - Marian Tonis; Wiwik Suryandartiwi; Tania Puteri Millenia (LPPM Universitas Awal Bros, 2021)
Safe and quality health services in hospitals have become the main hope and goal of the community/patients, health workers, hospital managers and owners as well as regulators. The services implemented in hospitals during the Covid-19 pandemic are called hospital services during the adaptation period for new habits. In this article, the author describes community service activities that have been carried out to increase public understanding of the flow of treatment services in hospitals and health protokols implemented in hospitals during the pandemic. Community service activities were carried out in RW 002 Kulim Village, Kulim District, Pekanbaru City, Riau Province by using the method of displaying service flowchart images in hospitals, lectures, to discussions and Q&A. As for the results of this community activity, the community has understood how the general flow of treatment services in hospitals is. The implementation of this activity is one form of support for the guidelines issued by the Ministry of Health of the Republic of Indonesia regarding technical guidelines for hospital services during the adaptation period of new habits. This activity can also provide new knowledge to the community regarding the flow of services and health protokols for patients in hospitals.